Systematic studies in the tribe Ericeae (Ericaceae-Ericoideae) - Oliver, E G H (Department of Biological Sciences, 2024)
[P. ii (abstract) missing]Ericaceae, to which the heaths and heathers belong, is a large widespread family comprising some 125 genera with 3000-4000 species (Sleumer 1966, Luteyn 1980). It has been divided up into several subfamilies and tribes and has included several other families, depending on the classification system being followed. The early treatments of genera were based on Linnaeus' Sexual System (Linnaeus 1753, 1754) in which 'Classes', sometimes unnatural groupings, occurred arid no families were defined, although many ericaceous genera were grouped together. The family Ericaceae was first proposed by Jussieu in 1789.